Synthesis of graphene/Cu2O thin film photoelectrode via facile hydrothermal method for photoelectrochemical measurement - Rosmahani Mohd Shah,; Rozan Mohamad Yunus,; Mohd Shahbudin Masdar @Mastar,; Lorna Jefferey Minggu,; Wai, Yin Wong; Abdul Amir H. Kadhum, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The process of carbon dioxide (CO2) reduction by using efficient non-precious-metal catalyst to make the process be economical has brought a comprehensive research in the area. In this study, graphene layer in copper foil was easily synthesized using hydrothermal method at temperature 200°C in 3 h duration. Diffraction peaks in XRD at around 29°, 36°, 42° and 74° in the composites correlate to the (110), (111), (200) and (311) crystalline planes of cubic cuprous oxide (Cu2O), while peak at 27° showed the carbon graphitic peak. Raman confirms the presence of the graphene layer on Cu2O. Photoelectrochemical performance test of Graphene/Cu2O demonstrated that the photoelectrocatalyst showing the photocurrent density 9.6 mA cm-2 at -0.8V vs Ag/AgCl. This study demonstrated a potential of semiconductor-based hybrid electrode for an efficient photoelectrocatalytic of CO2 reduction.